Price transmission in the pineapple market: What role for organic fruit? - Linda Kleemann; Alexandra Effenberger (Kiel Institute for the World Economy (IfW), 2010)
As consumers' demand for organic products and especially organic food grows, organic certification for tropical fruit is increasingly promoted in many developing countries. Certified organic pineapple exports only started taking off after 2005 and are rapidly increasing. The organic and conventional fresh pineapple value chains are dominated by certification standards and large multinational companies respectively. The two markets, however, still differ greatly in size. We analyze if this influences the price structure in these markets. Specifically, the paper attempts to single out the existence and direction of causality between the conventional and organic pineapple price using the European pineapple market as an example. We study spatial price transmission, i.e. the difference in prices between the markets for organic and conventional pineapple. The results indicate the dependence of organic market price movements on conventional ones. On the contrary, the conventional market is not affected by this niche market.
Keywords: F14; L11; L15; O13; Q13; Q17; 330; Price transmission; private standards; organic agriculture; organic markets; Tropische Frucht; Preisspanne; Biokost; Normung; Obstmarkt; Preis; Schätzung; Europa